2002
DOI: 10.1097/00004728-200211000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Change in Metabolic Response to Photic Stimulation of the Primary Visual Cortex in Infants: Functional Magnetic Resonance Imaging Study

Abstract: The blood oxygen level-dependent (BOLD) response to photic stimulation in the primary visual cortex (V1) reverses from positive to negative around 8 weeks of age. This phenomenon may be caused by increased oxygen consumption during stimulation as the result of a rapid increase of synaptic density at this age. To test this hypothesis, we applied existing mathematic models of BOLD signals to the experimental data from infants. When the stimulus-related increments of cerebral blood flow and cerebral blood volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 38 publications
3
23
0
3
Order By: Relevance
“…However Born et al [2002] have detected a decrease in perfusion on activation in sedated children aged 4 -71 months (in contrast to the increase observed in adults and usually assumed to be related to the increase in blood volume). It has been suggested that the change from positive to negative response is due to increased oxygen consumption during stimulation as a result of increased synaptic density, and the results of fitting neonatal data to mathematical models of the BOLD effect are consistent with this [Moramoto et al, 2002].…”
Section: Figurementioning
confidence: 75%
“…However Born et al [2002] have detected a decrease in perfusion on activation in sedated children aged 4 -71 months (in contrast to the increase observed in adults and usually assumed to be related to the increase in blood volume). It has been suggested that the change from positive to negative response is due to increased oxygen consumption during stimulation as a result of increased synaptic density, and the results of fitting neonatal data to mathematical models of the BOLD effect are consistent with this [Moramoto et al, 2002].…”
Section: Figurementioning
confidence: 75%
“…Previous studies using both NIRS and MRI have shown that light can sufficiently penetrate closed eyelids in both adults and infants to induce a measurable hemodynamic response over the visual cortex. 25,26 Visual stimulation was provided by a 19-in.-liquid crystal display Í‘LCDÍ’ monitor at a distance of 20 cm from the infant's face. The screen was placed over the top of the bassinet if the infant was lying supine.…”
Section: Protocolmentioning
confidence: 99%
“…These studies have mainly used sensory stimuli in the visual auditory or sensorimotor domain (Born et al 1998;Martin et al 1999;Yamada et al 1997;Muramoto et al 2002). Using passive somatosensorial stimulation, somatosensory areas have been identified in the precentral and postcentral gyri but showed weak hemispheric dominance as compared with the somatosensory system in adults (Erberich et al 2006).…”
Section: Functional Magnetic Resonance Imaging In Infantsmentioning
confidence: 99%